IMPACT OF WORK–LIFE BALANCE ON FEMALE EMPLOYEES AND ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM THE NIGERIAN BANKING SECTOR - Ogunbowale, Engr. Peter Enitan; Olufemi, Olayemi; Oyeleke, Bunmi Issaac (Journal of Business Studies and Management Review, 2025)
This study examined the impact of work–life balance (WLB) on female employees’ performance and overall organizational performance within the Nigerian banking sector. The study aimed to investigate how WLB practices such as flexible work arrangements, wellness programs, and supervisory support influence female employees’ performance and how this, in turn, affects organizational outcomes. It also tested whether female employee performance mediates the relationship between WLB and organizational performance. Data were obtained from 116 valid responses collected from female staff working in selected commercial banks across Lagos State. Descriptive and inferential statistics, including regression and bootstrap mediation analyses, were performed using SPSS. Results revealed that WLB significantly and positively influenced female employee performance (β = 0.366, p = 0.0008), while female employee performance significantly predicted organizational performance (β = 0.685, p < 0.001). The mediation analysis confirmed that employee performance mediates the relationship between WLB and organizational performance, with an indirect effect of 0.253 (95% CI [0.097, 0.441]) and an insignificant direct effect (β = 0.053, p = 0.4935). This indicates that WLB indirectly enhances organizational outcomes through improved employee performance. These findings indicated that WLB indirectly enhances organizational outcomes through improved employee performance. The study emphasized the importance of employee-centred WLB strategies for sustaining productivity and promoting organizational excellence in Nigeria’s banking industry.